Nationalism in Psychological Perspectives: An Analysis of Contemporary Dynamics and Relevance - Endah Andriani Pratiwi; Yoga Hardianto (SAINTIS Publishing, 2025)
Rapid social change and technological advances have influenced various dimensions of life, including in interpreting nationalism. In the post-Covid era full of challenges and uncertainties (Volatility, Uncertainty, Complexity, Ambiguity - VUCA), nationalism is no longer limited to physical struggle but requires adaptation to the context of the times. This study aims to examine the understanding and application of nationalism in the modern era from a psychological perspective, with a focus on how nationalism shapes individual identity and encourages contributions to national development. The research method used is Grounded Theory, which allows researchers to build theories based on empirical data collected from 138 respondents. Data were obtained through in-depth interviews and open-ended questionnaires, then analyzed using open, axial, and selective coding techniques to identify key themes related to nationalism. The study results show that nationalism in the modern era strengthens individual identity as part of the nation, increases pride in culture and history, and encourages active participation in social and economic development. In addition, nationalism plays a role in strengthening social solidarity, maintaining national stability, and facilitating adaptation to global change. This study concludes that nationalism in the post-Covid era must be understood as a dynamic ideology, which is not only rooted in history and national pride but also in the ability of individuals and organizations to innovate, adapt, and contribute to building the nation amidst global challenges.